Analysis of Students' Ability to Answer Reading Assessments with High Level Thinking Skills (Hots) - Muti'ah, Anggi; Reflinda, Reflinda; Melani, Melyann; Eliza, Eliza (Modality Journal: International Journal of Linguistics and Literature, 2023)
AbstractThis research is motivated by concerns about students' low ability to answer reading assessments with higher-order thinking skills (HOTS). Most of the issues that arise indicate that students' skill abilities are still low, and some students are not ready to face contextual problems, reasoning, situations that require creativity, all of which commonly occur in HOTS. The purpose of this research is to deepen understanding of students' abilities in the aspects of analysis, evaluation, and creation, which are key components of HOTS. The study was conducted on 30 eighth-grade students at Madrasah Tsanawiyah Negeri 02 Pasaman Barat as a representation of the population. The instrument used was a reading test consisting of 20 multiple-choice questions that measure three components of HOTS: analyzing, evaluating, and creating. The test indicators were adopted from Bloom's Taxonomy and Anderson. The research results show that students' high-order thinking abilities in answering reading assessments are sufficient. It can be seen from the average scores obtained by students in the analyzing component (64.66), evaluating (72.85), and creating (61.39), with an overall average for all components (66.3) falling into the "Sufficient" category. The implications of this research can provide guidance for the development of more effective learning strategies to enhance students' higher-order thinking skills in the context of reading.Keywords: Student Ability, Reading, Higher Order Thinking Skills (HOTS)Abstrak Penelitian ini dilatarbelakangi oleh kekhawatiran atas rendahnya kemampuan siswa dalam menjawab penilaian membaca dengan keterampilan berpikir tingkat tinggi (HOTS). Sebagian besar permasalahan yang muncul menunjukkan kemampuan keterampilan siswa masih rendah dan sebagian siswa belum siap menghadapi soal-soal kontekstual, penalaran, situasi yang membutuhkan kreativitas. Tujuan penelitian ini adalah untuk mendalami pemahaman tentang kemampuan siswa dalam aspek analisis, evaluasi, dan kreasi, yang merupakan komponen kunci dari HOTS. Penelitian ini dilakukan pada 30 siswa kelas VIII Madrasah Tsanawiyah Negeri 02 Pasaman Barat sebagai representasi populasi. Instrumen yang digunakan adalah tes membaca terdiri dari 20 soal pilihan ganda yang mengukur tiga komponen HOTS; menganalisis, mengevaluasi, dan mencipta. Indikator uji diadopsi dari Taksonomi Bloom dan Anderson. Hasil penelitian menunjukkan bahwa kemampuan berpikir tingkat tinggi siswa dalam menjawab penilaian membaca sudah cukup. Hal ini dibuktikan dengan nilai rata-rata yang diperoleh siswa pada komponen menganalisis (64,66), mengevaluasi (72,85), dan mencipta (61,39) dan rata-rata untuk seluruh komponen (66,3) adalah kategori Cukup. Implikasi dari penelitian ini dapat memberikan panduan untuk pengembangan strategi pembelajaran yang lebih efektif dalam meningkatkan keterampilan berpikir tingkat tinggi siswa dalam konteks membaca.Kata Kunci: Kemampuan Siswa, Membaca, Higher Order Thinking Skills (HOTS)